2017
DOI: 10.1111/bph.13833
|View full text |Cite
|
Sign up to set email alerts
|

Activation of AMP‐activated protein kinase by metformin ablates angiotensin II‐induced endoplasmic reticulum stress and hypertension in mice in vivo

Abstract: Metformin alleviates Ang II-triggered hypertension in mice by activating AMPKα2, which mediates phospholamban phosphorylation and inhibits Ang II-induced ER stress in vascular smooth muscle cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 79 publications
2
30
1
Order By: Relevance
“…In Nagata et al's [91] research, they found that AngII could activate AMPK, but the test was performed within 1 h, and if they extend the duration of action, will the results change? In another study, low concentrations (0.1-1 μM) of AngII led to minor activation of AMPK, whereas high concentrations (5 μM) of AngII decreased AMPKα phosphorylation in human VSMCs [93]. We hypothesize that AngII activates AMPK at a small initial dose and protects it.…”
Section: Angii and Ampk In Kidneymentioning
confidence: 80%
See 1 more Smart Citation
“…In Nagata et al's [91] research, they found that AngII could activate AMPK, but the test was performed within 1 h, and if they extend the duration of action, will the results change? In another study, low concentrations (0.1-1 μM) of AngII led to minor activation of AMPK, whereas high concentrations (5 μM) of AngII decreased AMPKα phosphorylation in human VSMCs [93]. We hypothesize that AngII activates AMPK at a small initial dose and protects it.…”
Section: Angii and Ampk In Kidneymentioning
confidence: 80%
“…While they did not detect the RAS components in this experiment. Later studies showed that when the treating time and concentration are sufficient, AngII tended to suppress the activity of AMPK [92,93]. There was another study, which declaimed AngII could elevate LKB1 expression in VSMCs and neointima.…”
Section: Angii and Ampk In The Vascular Systemmentioning
confidence: 99%
“…28 Metformin treatment decreases angiotensin II-induced ER stress and hypertension in mice through activation of AMPK. 29 Metformin also decreases β-cell lipotoxicity through inhibition of the ER stress. 30 Pathologic ER stress leads to calcium release, which is directed toward the mitochondria via domains shared by ER and mitochondria called mitochondria-associated membranes (MAM).…”
mentioning
confidence: 99%
“…This phosphorylation results in abnormal N-glycosylation of PD-L1 and prevents its development within the Golgi apparatus and degradation in endoplasmic reticulum. Therefore, metformin causes malignant cells to be more susceptible to cytotoxic T cells (19)(20)(21)(22).…”
Section: Methodsmentioning
confidence: 99%